Examining the relations between Turkish students' personality characteristics and internet attitudes and use - (:unkn) unknown (My University, 2007)
Internet has created many conveniences and opportunities for individuals in the society today. However, the impact of internet is not fully understood in spite of widespread implementation, especially in terms of psychological researches. In this study, the relationships between Turkish students' personality characteristics and internet attitudes and use were examined. A survey method was used for the study and the sample consisted of 201 students from the university of Marmara University, Istanbul. A five-point likert type scale was used in order to measure the internet attitudes and a questionnaire was distributed to the participants to collect information about demographic information and internet use. To determine the personality characteristics, adjective check list was used. At the end of the study, significant relationships found between Turkish students' personality characteristics and internet attitudes and use. Also, the findings revealed that Turkish students' personality characteristics were related to their internet attitudes, and explain about 51% of the total variance of the internet attitudes. Moreover some of personality characteristics such as order, heterosexuality, autonomy, aggression, succorance, abasement, self-control and self-confidence significantly predicted students' internet attitudes.
Keywords: Internet attitudes; Internet use; Personality; Personality characteristics